Perancangan Pengendali Mesin Teabags Otomatis Pembuat Teh Kelor (Moringa Oleifera) Menggunakan Pengendali PLC (Programmable Logic Controller) Mitsubishi FX3U 24MR - Ananda Nur Hidayat; Paniran; Budi Dermawan (Bulletin of Computer Science Research, 2024)
Moringa plant (Moringa oleifera) is known as “The Miracle Plant” due to its nutrient content and extensive health benefits. This research discusses the design and implementation of an automation system for the production of Moringa (Moringa oleifera) tea bags using a Mitsubishi FX3U 24MR Programmable Logic Controller (PLC). Moringa is a tropical food crop with high nutritional value and therapeutic benefits. With the increasing demand for tea bags, an efficient production system is needed to increase productivity and reduce costs. This research designs an automatic teabags machine that utilizes PLC to control various components in the production process, including grinding machine, mixer machine, and oven machine. The research method includes designing PLC hardware and software schematics, testing components, and analyzing test result data. The results show that the PLC system is effective in controlling the production process, improving efficiency and product quality, and reducing the involvement of human labor. The conclusion of this research is that the use of PLC in the moringa teabag production automation system offers an efficient solution, the speed of the ac motor can be adjusted through giving the setting value of PWM which affects the motor terminal voltage (Vt), the greater the PWM setting value, the higher the number of motor rotations (rpm). Vice versa, the smaller the PWM setting value, the lower the number of motor revolutions (rpm).